2014
DOI: 10.3390/molecules191221044
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal Activity against Entamoeba histolytica of Plants Used in Northeast Mexican Traditional Medicine. Bioactive Compounds from Lippia graveolens and Ruta chalepensis

Abstract: Amoebiasis caused by Entamoeba histolytica is associated with high morbidity and mortality is becoming a major public health problem worldwide, especially in developing countries. Because of the side-effects and the resistance that pathogenic protozoa build against the standard antiparasitic drugs, e.g., metronidazole, much recent attention has been paid to plants used in traditional medicine around the world in order to find new antiprotozoal agents. We collected 32 plants used in Northeast Mexican traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 115 publications
3
38
0
1
Order By: Relevance
“…Although the mechanism of antiprotozoal action of carvacrol is not well known, this compound showed good results in the growth inhibition of protozoa such as T. cruzi, T. brucei rhodesiense, Leishmania chagasi and Plasmodium falciparum. Furthermore, the methanolic extract of Lippia graveolens, containing carvacrol, inhibits the growth of Entamoeba histolytica [21]. It has been shown that β-pinene has antibacterial activity [22] and this monoterpene was present in various essential oils with leishmanicidal activity [23].…”
mentioning
confidence: 99%
“…Although the mechanism of antiprotozoal action of carvacrol is not well known, this compound showed good results in the growth inhibition of protozoa such as T. cruzi, T. brucei rhodesiense, Leishmania chagasi and Plasmodium falciparum. Furthermore, the methanolic extract of Lippia graveolens, containing carvacrol, inhibits the growth of Entamoeba histolytica [21]. It has been shown that β-pinene has antibacterial activity [22] and this monoterpene was present in various essential oils with leishmanicidal activity [23].…”
mentioning
confidence: 99%
“…In addition, substances such as linoleic, linolenic, oleanolic, betulinic acids, betulin, and beta-sitosterol glucoside, among others, were reported to suppress adherence of S. mutans in-vitro (Wu, 2009). Chalepensin (Figure 1), previously isolated and identified (Quintanilla-Licea et al, 2014), can be found particularly in plants of the Rutaceae family (Günaydin and Savci, 2005), with reported anti-fertility (Kong et al, 1989), antitumor (Wu et al, 2003), and antiplatelet aggregation (Lv et al, 2015) activities. In the present study, we showed for the first time evidence of the in vitro antimicrobial effect of chalepensin, isolated from R. chalepensis, against S. mutans, which broadens its spectrum of biological activity and provides the basis for further validation in pre-clinical studies.…”
Section: Discussionmentioning
confidence: 96%
“…Chalepensin was extracted and identified as previously reported (Quintanilla-Licea et al, 2014). R. chalepensis pulverized leaves (600 g) were extracted during 40 h, using methanol in a Soxhlet equipment.…”
Section: Isolation and Identification Of Chalepensinmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that this infection is prevalent in Asia, Africa, South and Central America [12]. The poor hygienic conditions and environmental pollution have been shown to strengthen amoebic infections [13]. Mostly the amoebic cases are reported from developing countries and are introduced to developed countries due to the moments of human and animals [14].…”
Section: Introductionmentioning
confidence: 99%